2014
DOI: 10.1128/aem.02964-13
|View full text |Cite
|
Sign up to set email alerts
|

UV Light Inactivation of Human and Plant Pathogens in Unfiltered Surface Irrigation Water

Abstract: bFruit and vegetable growers continually battle plant diseases and food safety concerns. Surface water is commonly used in the production of fruits and vegetables and can harbor both human-and plant-pathogenic microorganisms that can contaminate crops when used for irrigation or other agricultural purposes. Treatment methods for surface water are currently limited, and there is a need for suitable treatment options. A liquid-processing unit that uses UV light for the decontamination of turbid juices was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 20 publications
2
38
2
Order By: Relevance
“…Groundwater sources are generally considered less vulnerable to contamination by pathogenic microorganisms, while surface water and wastewater have a much higher potential for contamination. Farmers utilizing surface water for food crops, which are consumed raw should follow proper mitigation strategies to control contamination [132]. The method utilized for irrigation has a substantive role in pathogenic contamination of crops.…”
Section: Pathogensmentioning
confidence: 99%
“…Groundwater sources are generally considered less vulnerable to contamination by pathogenic microorganisms, while surface water and wastewater have a much higher potential for contamination. Farmers utilizing surface water for food crops, which are consumed raw should follow proper mitigation strategies to control contamination [132]. The method utilized for irrigation has a substantive role in pathogenic contamination of crops.…”
Section: Pathogensmentioning
confidence: 99%
“…This indicated that the efficacy of the UV-C decreased with an increase in the turbidity of water. High levels of turbidity in water could affect the transmittance of UV light, influencing the efficacy of the UV-C treatment (Jones et al, 2014;Koutchma et al, 2009). The suspended particles in water can absorb and scatter the UV light, subsequently reducing disinfection efficacy (Andreadakis, Mamais, Christoulas, & Kabylafka, 1999;Jolis, Lam, & Pitt, 2001).…”
Section: Ta B L E 3 Reduction Of Genericmentioning
confidence: 99%
“…As the turbidity of groundwater and surface water is generally higher than municipal water (Topalcengiz, Strawn, & Danyluk, 2017), the efficacy of UV-C in these waters could be different. This study used a large volume of surface water and well water to simulate a water treatment system in agricultural settings (Jones, Worobo, & Smart, 2014). This study evaluated the efficacy of UV-C light treatment in reducing generic E. coli in surface water, well water, and their mixtures with different level of turbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available solutions found for these concerns are chemical disinfection such as sodium hypochlorite and calcium hypochlorite, UV-C light, filtration, electrochemical disinfection and ultrasounds (US) among others (Jones et al, 2014;Norton-Brandão et al, 2013). Among these methods, the efficacy of chlorination has been widely reported as the main technology used for the removal of biohazards to disinfect irrigation water (Suslow, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If the irrigation water is obtained from a surface water reservoir, it is considered as a high risk for pathogen contamination with foodborne pathogens such as Salmonella spp. and pathogenic Escherichia coli, because they are open to many routes by which microorganism causing plant disease or human food-borne illness can enter (Jones, Worobo, & Smart, 2014). This is the case of most of the irrigation water used in the south-east production area of Spain (Castro-Ibáñez, Gil, Tudela, Ivanek, & Allende, 2015).…”
Section: Introductionmentioning
confidence: 99%